2006
DOI: 10.1021/ac0516988
|View full text |Cite
|
Sign up to set email alerts
|

A Simple, Valveless Microfluidic Sample Preparation Device for Extraction and Amplification of DNA from Nanoliter-Volume Samples

Abstract: A glass microdevice has been constructed for the on-line integration of solid-phase extraction (SPE) of DNA and polymerase chain reaction (PCR) on a single chip. The chromatography required for SPE in the microfluidic sample preparation device (muSPD) was carried out in a silica bead/sol-gel SPE bed, where the purified DNA was eluted directly into a downstream chamber where conventional thermocycling allowed for PCR amplification of specific DNA target sequences. Through rapid, simple passivation of the PCR ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
146
1
5

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(153 citation statements)
references
References 35 publications
1
146
1
5
Order By: Relevance
“…T here has thus been an effort to develop low-cost, automated diagnostic biosensors (e.g. nanotechnology-based sensors (Zhang et al 2005) or microfluidic systems, such as droplet -based , Chiou et al 2013, centrifugal (Cho et al 2007), paper (Martinez et al 2009, Fu et al 2010, Zuo et al 2013, capillary (T akayama et al 1999, Yager et al 2008, Gervais and Delamarche 2009, pneumatic (Legendre et al 2006, Mohan et al 2013 devices and lateral flow assays (Yager et al 2008, Chen et al 2010, You et al 2011). For the past decade, this has led to numerous publications about promising, early-stage technologies (Baeumner et al 2003, Leonard et al 2003, Kost 2006, Lazcka et al 2007, Lucchi et al 2010, Asiello and Baeumner 2011, Duarte et al 2011, Karlsson et al 2011, Schudel et al 2011, Matlock-Colangelo and Baeumner 2012, Lounsbury et al 2013, Mohan et al 2013.…”
Section: Introductionmentioning
confidence: 99%
“…T here has thus been an effort to develop low-cost, automated diagnostic biosensors (e.g. nanotechnology-based sensors (Zhang et al 2005) or microfluidic systems, such as droplet -based , Chiou et al 2013, centrifugal (Cho et al 2007), paper (Martinez et al 2009, Fu et al 2010, Zuo et al 2013, capillary (T akayama et al 1999, Yager et al 2008, Gervais and Delamarche 2009, pneumatic (Legendre et al 2006, Mohan et al 2013 devices and lateral flow assays (Yager et al 2008, Chen et al 2010, You et al 2011). For the past decade, this has led to numerous publications about promising, early-stage technologies (Baeumner et al 2003, Leonard et al 2003, Kost 2006, Lazcka et al 2007, Lucchi et al 2010, Asiello and Baeumner 2011, Duarte et al 2011, Karlsson et al 2011, Schudel et al 2011, Matlock-Colangelo and Baeumner 2012, Lounsbury et al 2013, Mohan et al 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Such a development will be valuable for emergency responders, criminal investigators and forensic identification. In this work, electrical lysis of biological cells is investigated with a commonly used microchannel structure, where the electrode with excitation potential is positioned at one end of the microchannel, whereas the electrode at the other end of the microchannel is grounded [5][6][7][8][9][10]. The novelty of this work is the analysis of the estimation errors of electric fields of typical microfluidic devices used in such experiments and the models to reduce such estimation errors to achieve a high yield, which is critical for single-cell analysis.…”
Section: Introductionmentioning
confidence: 99%
“…This is the most commonly used expression to estimate the electric field strengths inside the microchannels of microfluidic devices [5][6][7][8][9], even though the assumptions involving dielectric constant, fringe field and parallel electrode surface are invalidated. Furthermore, solid-liquid interface develops an electrical double layer (EDL) with the characteristic thickness of the Debye length, which has significant influence on the behavior of ionic conductors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both high concentration salts and organic solvents are potent inhibitors to the downstream processes such as PCR. Legendre et al [18] reported that DNA in the initial fraction eluted from the silica beads was poorly amplified, and thus a longer elution time was required to remove the residual inhibitors. Witek et al [19] removed ethanol by drying the extraction device with nitrogen gas before the elution step.…”
Section: Introductionmentioning
confidence: 99%